Efforts to Resolve Agricultural Land Ownership in Absentee Cases in Blitar Regency - Adam, Ferry; Al-Anshori, Huzaimah; Manfaluthi, Agus (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze agricultural land ownership in absentee cases, which constitutes one of the agrarian issues potentially hindering increased productivity and farmers’ welfare. Absentee practices still occur in Blitar Regency. The academic problems addressed in this study are: 1) How are efforts to resolve absentee agricultural land ownership carried out by the government and related agencies in Blitar Regency? 2) What obstacles are encountered in the efforts to resolve absentee agricultural land ownership in Blitar Regency? The research employs a normative sociological approach, with data obtained through both fieldwork and literature studies, including primary and secondary sources. Data collection techniques include interviews, literature review, and document analysis. This study used descriptive qualitative analysis. This study showed two results. The first efforts to resolve the issue include land data inventory, administration of ownership transfer regulation, legal socialization, and land redistribution under the agrarian reform program. Legal prohibitions have been stipulated in Law No. 5 of 1960 concerning the Basic Agrarian Principles and clarified through Government Regulation No. 224 of 1961 in conjunction with Government Regulation No. 4 of 1977. The contributing factors include urbanization, the inheritance of land by heirs residing at a distance, and changes in the occupations of landowners. The second, obstacles such as limited data, suboptimal inter-agency coordination, and low public legal awareness still impede effective handling. Therefore, it is essential to strengthen administrative regulations, enhance inter-agency coordination, and ensure consistent law enforcement to achieve agrarian justice in Blitar Regency.